Human health risk assessment of groundwater nitrogen pollution in Jinghui canal irrigation area of the loess region, northwest China - Zhang, Yuting; Wu, Jianhua; Xu, Bin (Environmental earth sciences, 2018)
Nitrogen pollution of groundwater is becoming more and more serious due to intense and extensive industrial and agricultural activities. This may exert great influence on human health. In this paper, human health risk due to groundwater nitrogen pollution in Jinghui canal irrigation area in Shaanxi Province of China where agricultural activities are intense was assessed. Forty-seven groundwater samples were collected from shallow wells and analyzed for physicochemical indices in the study area. Water samples were analyzed for pH, total dissolved solids (TDS), total hardness (TH), major ions (Na + , K + , Ca 2+ , Mg 2+ , HCO 3− , CO 3 2− , Cl − and SO 4 2− ), nitrate (NO 3 –N), nitrite (NO 2 –N) and ammonia nitrogen (NH 4 –N). General groundwater chemistry was described by statistical analysis and the Piper diagram. Water quality was quantified via comprehensive water quality index (CWQI), and human health risk was assessed considering the age and exposure pathways of the consumers. The results show that the shallow groundwater is slightly alkaline and groundwater types are HCO 3 ·SO 4 ·Cl–Mg and HCO 3 ·SO 4 ·Cl–Na. Rock weathering and evaporation are main natural processes regulating the groundwater chemistry. The CWQI indicates that groundwater in the study area is seriously polluted by TH, TDS, SO 4 2− , Cl − and NO 3 − . Human health risk is high because of high concentrations of nitrate in drinking water. The results also show that children are at higher risk than adults. The health risk through dermal contact is much lower than that through drinking water intake and can be ignored.